Use of X-ray microtomography and full-field image correlation tools for the thermomechanical analysis of high temperature material behaviours - Bao, Jianguang (2021)
This research is geared toward exploring the physical mechanisms occurring during the deformation process of high temperature engineering materials, viz. the SLM AlSi10Mg alloy and the FV566 stainless steel. The thermomechanical behaviour of the SLM AlSi10Mg alloy and FV566 stainless steel was studied by conducting many experimental investigations. Conventional cyclic and creep-cyclic tests were performed on the SLM AlSi10Mg alloy specimens under high temperature conditions to study the mechanical response, microstructure evolution as well as the role of temperature and SLM defects on the high temperature cyclic behaviour of the SLM AlSi10Mg alloys. The effects of low cycle fatigue and creep, as well as their interactions during combined cycling, have been investigated further to improve the understanding of the mechanisms responsible for material degradation. In-situ high-stress ratio tensile-tensile low cycle fatigue tests at both room and elevated temperatures were also carried on the SLM AlSi10Mg alloy specimens through a time-lapse synchrotron radiation X-raycomputed microtomography to study fatigue damage accumulation arising from internal defects during tensile-tensile cycling. To follow the defect kinetics during the entire cyclic life, an in-situ high temperature cyclic test rig was designed to accommodate the synchrotron radiation beamline. Besides, high temperature tensile and short-term creep tests have been performed on the FV566 stainless steel specimens with different geometries to understand the governing deformation mechanisms and the real rate-controlling creep mechanisms. To track high temperature strain heterogeneities at both uniaxial and biaxial stress states, a homemade high temperature digital image correlation system was developed. The microstructure changes as well as deformation and damage mechanisms of both materials were investigated by several quantitative imaging techniques. These include optical microscopy, scanning electron microscopy, electron backscatter diffraction, energy dispersive spectrometer, X-Ray diffraction and Laboratory X-ray computed microtomography. These mapping tools have enabled to obtain information at the initial and ruptured states regarding changes of microstructure features including the crystallographic orientations, grain sizes, phases, local misorientation, the morphologies as well as defect sizes and locations.